(untitled) (Innovative professional education, 2025)
This article describes trends and improve the educational process of future skilled workers building structure using modern means of education; describes the concept, content and context of professional competence of future builder; the problems of training future skilled workers building profiles based on advanced vocational schools; Builders of continuing education; discussed the possibility of forming professional competence of skilled workers building structure during the manufacturing training in university and industrial practice in terms of construction companies and enterprises; defined the essence of professional competence builder that appropriate rozhlyaduvaty the unity of theoretical and practical preparedness activities in the construction sector